Buprenorphine Induction in a Rural Maryland Detention Center During COVID-19: Implementation and Preliminary Outcomes of a Novel Telemedicine Treatment Program for Incarcerated Individuals With Opioid Use Disorder - Belcher, Annabelle M.; Coble, Kelly; Cole, Thomas O.; Welsh, Christopher J.; Whitney, Anna; Weintraub, Eric (Frontiers in Psychiatry, 2021)
Over 10 million individuals pass through U.S. detention centers on an annual basis, with nearly two-thirds meeting criteria for drug dependence/abuse. Despite proven efficacy, treatment with medications for opioid use disorder (MOUD) is underutilized in jail settings—a gap that could be addressed using telemedicine. Here we describe a new program of telemedicine-based clinical provision of new/continuing buprenorphine treatment for individuals detained in a rural jail. Implementation objectives were completed between January and August 2020, and patient encounters were conducted between August 2020 and February 2021. We established (i) telemedicine hardware/software capability; (ii) a screening process; (iii) buprenorphine administration methods; (iv) necessary medical release procedures; (iv) telemedicine encounter coordination and medication prescription procedures; and (v) a research platform. Seven incarcerated patients have been treated, two of whom were referred from community treatment. Patients were mostly male (71%), non-Hispanic White (86%), and averaged 33 years old. All patients tested positive for an opioid upon intake and began/continued buprenorphine treatment in the jail. Average time to first MOUD appointment was 9 days and patients were maintained in treatment an average 21 days. Referrals for continuing community treatment were offered to all patients prior to discharge. We report successful implementation of telemedicine MOUD in a rural detention center, with treatment engagement and initiation occurring prior to the high-risk period of discharge. The fact that this program was launched during the height of the pandemic highlights the flexibility of telemedicine-based MOUD (tMOUD). Challenges and obstacles to implementation of tMOUD in a correctional system are discussed.